Ophiobolin-O Reverses Adriamycin Resistance via Cell Cycle Arrest and Apoptosis Sensitization in Adriamycin-Resistant Human Breast Carcinoma (MCF-7/ADR) Cells - Weiming Zhu; Caiguo Huang; Kui Hong; Jieyin Sun; Shanjian Wei; Xue Yang; Tonghan Zhu; Cuiting Lv; Wenxia Sun (Marine Drugs, 2013)
Multidrug-resistance is a major obstacle facing cancer chemotherapy. This paper demonstrates that novel compound Ophiobolin-O reverses MCF-7/ADR resistance to adriamycin (ADM). The IC50 of ADM treated MCF-7 cells was 2.02 ± 0.05 µM and 74.00 ± 0.18 µM treated MCF-7/ADR cells, about 37-fold, compared to the former. However, 0.1 µM Ophiobolin-O (less than 20% inhibition concentration) combined with ADM caused the decreased IC50 of ADM to 6.67 ± 0.98 µM, indicating it reversed ADM resistance of MCF-7/ADR cells (11-fold). Furthermore, Ophiobolin-O increased ADM-induced mitochondrial pathway apoptosis and G2/M phase arrest, which is partly due to the elevation level of ROS in MCF-7/ADR cells. As we described in this paper, the reversal effect of Ophiobolin-O may be due to the reduction of resistance-related protein P-Glycoprotein (P-gp, also known as MDR1) through inhibiting the activity of the multidrug resistance 1 (MDR1) gene promoter, which makes MCF-7/ADR cells more sensitive to ADM treatment. Assays in nude mice also showed that the combination of ADM and Ophiobolin-O significantly improved the effect of ADM.